A PILOT CLINICAL TRIAL TO MONITOR RESPONSE TO CHEMOTHERAPY USING THE CA-62 MARKER OF EPITHELIAL CARCINOMAS - G. G. Khakimova; Zh. R. Cherkasova; S. A. Tsurkan; G. A. Fedchikov; N. V. Suganov; V. A. Gorbunova (Сибирский онкологический журнал)
The objective of the study was to assess the feasibility of using CA -62 marker of epithelial carcinomas for monitoring treatment response and detecting cancer progression or recurrence during chemotherapy.Material and Methods. A 12-month double-blind clinical trial was conducted by two independent groups: clinical oncologists and biochemists, and involved 89 patients with different cancers confirmed by histopathological findings. The other inclusion criteria were: the presence of at least one measurable lesion according to the RECIST criteria, ECOG performance status 0-2 and satisfactory laboratory parameters. The expression of CA -62 cancer marker was measured by immunochemiluminescent assay used for the detection of epithelial carcinomas.Results. The elevated level of CA -62 marker was observed in 76 patients before starting the treatment. After completion chemotherapy, the level of this marker decreased to the normal reference ranges (<4600 U/ml) in 53 % of patients and remained increased in 24 % of patients. Of 24 % of patients with the initial low level of CA -62 marker (1000–4000 U/ml) before treatment, 12 % had no changes in the level of this marker during chemotherapy; however, 5 % of these patients had disease progression and 7 % had stable disease after starting the treatment. In 12 % of patients with an initial low CA -62 level, it increased during chemotherapy, indicating disease progression.Conclusion. The changes in the level of CA -62 marker during chemotherapy in patients with gastric cancer, small-cell lung cancer, colorectal cancer, neuroendocrine cancer and ovarian cancer showed a high correlation (76–100 % depending on the tumor site) with the performance status of the patients according to RECIST criteria. The CA -62 marker was shown to be feasible for monitoring gastric cancer, small-cell lung cancer, colorectal cancer, neuroendocrine cancer and ovarian cancer as well as for assessing the response to chemotherapy.